Photoreceptor cells as a source of fundus autofluorescence in recessive Stargardt disease. Issue 1 (27th April 2018) - Paavo, Maarjaliis; Lee, Winston; Allikmets, Rando; Tsang, Stephen; Sparrow, Janet R.
Abstract: Bisretinoid fluorophores form in photoreceptor outer segments from nonenzymatic reactions of vitamin A aldehyde. The short‐wavelength autofluorescence (SW‐AF) of fundus flecks in recessive Stargardt disease (STGD1) suggests a connection to these fluorophores. Through multimodal imaging, we sought to elucidate this link. Flecks observed in SW‐AF images often colocalized with foci exhibiting reduced or absent near‐infrared autofluorescence signal, the source of which is melanin in retinal pigment epithelial (RPE) cells. With serial imaging, changes in near‐infrared autofluorescence (NIR‐AF) preceded the onset of fleck hyperautofluorescence in SW‐AF images and fleck profiles in NIR‐AF images tended to be larger. Flecks in SW‐AF and NIR‐AF images also corresponded to hyperreflective lesions traversing photoreceptor‐attributable bands in horizontal SD‐OCT scans. The hyperreflective lesions interrupted adjacent OCT reflectivity bands and were associated with thinning of the outer nuclear layer. These SD‐OCT findings are attributable to photoreceptor cell degeneration. Progressive increases and decreases in the SW‐AF intensity of flecks were evident in color‐coded quantitative fundus autofluorescence maps. In some cases, flecks appeared to spread radially from the fovea to approximately 8° of eccentricity, beyond which a circumferential spread characterized the distribution. Since the NIR‐AF signal is derived from melanin and loss of this autofluorescence is indicative of RPE atrophy, the SW‐AF of flecks cannot be accounted for by bisretinoid lipofuscin in RPE. Instead, we suggest that the bisretinoid serving as the source of the SW‐AF signal, resides in photoreceptors, the cell that is also the site of bisretinoid synthesis. Abstract : In recessive Stargardt disease, a early onset form of macular degeneration, hyperautofluorescent foci are often features of short wavelength fundus autofluorescence. In color‐coded quantitative autofluorescence maps the distributions and intensity changes of these flecks are apparent. We provide evidence that flecks are a manifestation of groups of degenerating photoreceptor cells.